2019
DOI: 10.1038/s41591-019-0652-7
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity sequencing reveals the sources of plasma circulating cell-free DNA variants

Abstract: Accurate identification of tumor-derived somatic variants in plasma circulating cell-free DNA (cfDNA) requires understanding the various biologic compartments contributing to the cfDNA pool. We sought to define the technical feasibility of a high-intensity sequencing assay of cfDNA and matched white-blood cell (WBC) DNA covering a large genomic region (508 genes, 2Mb, >60,000X raw-depth) in a prospective study of 124 metastatic cancer patients, with contemporaneous matched tumor tissue biopsies, and 47 non-can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
484
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 541 publications
(531 citation statements)
references
References 64 publications
14
484
2
4
Order By: Relevance
“…During the process of aging different mutations accumulate in hematopoietic stem cells. This phenomenon occurs frequently in the elderly and its prevalence has been estimated at 31% [39]. The mutations resulting from clonal hematopoiesis are often detected during cfDNA sequencing analysis, since the majority of cfDNA is derived from leukocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the process of aging different mutations accumulate in hematopoietic stem cells. This phenomenon occurs frequently in the elderly and its prevalence has been estimated at 31% [39]. The mutations resulting from clonal hematopoiesis are often detected during cfDNA sequencing analysis, since the majority of cfDNA is derived from leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The mutations resulting from clonal hematopoiesis are often detected during cfDNA sequencing analysis, since the majority of cfDNA is derived from leukocytes. Recently, it has been demonstrated that 53.2% of all mutations detected by cfDNA sequencing analysis result from clonal hematopoiesis, indicating the need for collection and sequencing of leukocytes as a reference [39].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have suggested that CH mutations present a challenge for proper filtering in highly sensitive NGS-based liquid biopsy assays [26][27][28] . We observed that the use of patient-matched normal WBC DNA in MSK-ACCESS eliminated 7,760 (77%) of variant calls below 10% VAF (Figure 4A-IV).…”
Section: Assessing the Filtering Of Putative Clonal Hematopoiesis (Chmentioning
confidence: 99%
“…In summary, the recent achievements in high-sensitive sequencing methodologies of pretreatment plasma ccfDNA have proven to become an useful tool to detect and map tumor-derived mutations and offer opportunities as those reported by Kruger and colleagues, to investigate the clinical value for the prediction of therapy response and clinical outcome. However, these same high-sensitive sequencing methodologies now also visualize that most variants detected in ccfDNA of cancer patients represent especially CHIP and that CHIP is more prevalent than was previously anticipated (Chen et al, 2019;Razavi et al, 2019). In particular, this high prevalence of CHIP emphasizes the importance of parallel high-sensitive sequencing of DNA derived from WBCs of the same patient for appropriate variant interpretation.…”
mentioning
confidence: 90%